2020
DOI: 10.21203/rs.3.rs-55497/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of a Benign Prostatic Hyperplasia (BPH) Xenobiotic - Croton membranaceus Müll.Arg. Root Extract on CYP1A2, CYP3A4, CYP2D6, and GSTM1 Drug Metabolizing Enzymes in Rat Model

Abstract: Background Croton membranaceus Müll.Arg., root extract has been scientifically and clinically proven to be efficacious in the management of BPH. However, its effect on liver drug-metabolizing enzymes has not been established. This study aimed to determine the effect of the plant extract on phase I and phase II drug-metabolizing enzymes. Materials and methods Fifteen (15) castrated testosterone-induce BPH male Albino Wister rats weighing between 120–150 grams were randomly divided into 3 groups of 5 rats eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…The bulb also treats cancer in the Limpopo Province of South Africa [40]. Several ethnobotanica surveys have shown that the B. volubilis bulb relieves gastrointestinal problems [42][43][44][45] Cimi and Campbell [46] report that the plant is used to treat kidney problems in Ma khanda (former Grahamstown). The use of this plant for urinary tract infections has been reported by Philander [23], Cock [47], and Coopoosamy and Naidoo [48].…”
Section: Traditional Use Of B Volubilismentioning
confidence: 99%
See 1 more Smart Citation
“…The bulb also treats cancer in the Limpopo Province of South Africa [40]. Several ethnobotanica surveys have shown that the B. volubilis bulb relieves gastrointestinal problems [42][43][44][45] Cimi and Campbell [46] report that the plant is used to treat kidney problems in Ma khanda (former Grahamstown). The use of this plant for urinary tract infections has been reported by Philander [23], Cock [47], and Coopoosamy and Naidoo [48].…”
Section: Traditional Use Of B Volubilismentioning
confidence: 99%
“…Madikizela et al [52] list B. volubilis as one of the plant species used to treat tuberculosis in Pondoland, South Africa. B. volubilis is used as a topical med ication for various skin or mucous membrane diseases [23,38,40,45,48], as well as infection of the eye [23,36,47,48]. Furthermore, liver problems are managed using B. volubilis [36] Certain problems associated with pregnancy and childbirth are treated with medicines made from the bulbs of B. volubilis [23,35,48,53,54].…”
Section: Traditional Use Of B Volubilismentioning
confidence: 99%